Enhanced Transport and Permeation of a Polymeric Nanocarrier across the Retina by Mixing with ATP upon Intravitreal Injection - Kiyoon Kwon; Youngmin Hwang; Junyoung Jung; Giyoong Tae (MDPI AG, 2021)
The outer part of the retina pigment epithelium (RPE) in the retina is the main site of neovascularization associated with retinal diseases. However, various obstacles interrupt the delivery of medicines across the RPE, mainly due to the well-developed tight junctions in the RPE. Currently, there is no practical formulation to overcome this issue. In this study, we demonstrated that simple mixing with adenosine tetraphosphate (ATP) has the potential to greatly enhance the transport and permeation of a polymeric nanocarrier across the retina via intravitreal administration. Chitosan-functionalized, pluronic-based nanocarrier (NC), which can deliver various biomolecules efficiently, was used as a polymeric nanocarrier. Mixing with ATP facilitated the diffusion of the nanocarrier in the vitreous humor by reducing the electrostatic interaction between NC and negatively charged glycosaminoglycans (GAGs) in the vitreous humor. Mixing with ATP also allowed the penetration of NC across the whole retina, and it resulted in a great increase (approximately nine times) in the transport of NC across the retina, as well as spreading it throughout the whole retina upon intravitreal administration in a mouse model. This enhanced permeation across the retina was specific to ATP but not to GTP, suggesting the possibility of P2Y receptor-mediated tight junction disruption by ATP.